Pelayanan Administrasi E-KTP Di Kecamatan Palu Barat Kota Palu - Fachrul Reza; Titik Ermiyati (Jurnal ADMINISTRATOR, 2020)
This research concerning the quality of administrative services of E-KTP in sub-district Palu Barat. The informant in this research chosen by using purposive sampling. And used primary and secondary data that obtained from the result of interview and investigation. The data analysis that used in this research was descriptive qualitative. Based on the result of the research by using 3 (three) indicator of the quality of administrative services E-KTP in Palu Barat sub-district Palu, so the dimention/aspect of administrative services related to public service assessment which includes; reliability, responsibility, and warranty. Related to reliability and responsibility are goes well while warranty is not going well.